Hope in the uncertainties and certainty for parents of children with rare neurological disorders: Part 3 (of 3): Hope. (5th September 2022) - Bye, Ann ME; Le Marne, Fleur A; Beavis, Erin; Macintosh, Rebecca; Nevin, Suzanne M; Palmer, Elizabeth E; Sachdev, Rani; Nunn, Kenneth
Abstract : This is the third article of a three‐part series and addresses how clinicians provide hopefulness meaningfully to families coping with life‐limiting and quality of life impairing neurological conditions. The first two articles addressed the enormous challenges faced by carers and also explored the struggles of clinicians trying to provide relief and comfort. Can these families, and those helping clinically, legitimately hope? It is expectation that consolidates desire into a substantial hope that may motivate finding a way forward. Hope must be realistic and directed to something in particular and in someone in particular. Hope and despair are not monolithic but often travel together for both children, families and clinicians. Hope is not denial but a belief that there are positive possibilities. Finding what can be helpfully hoped for and what must be realistically despaired of, is the discerning struggle. Clinicians aim to change what we can and accept what we cannot. Acceptance and grief are arrived at slowly for carers and families. Similarly, clinicians struggle with the hopes of bringing meaningful solace and are supported by trusted colleagues who have shared the same experience. Clinicians strive to respond appropriately and effectively in a dynamic process based on trust, providing presence and compassion when cure is not possible. Clinicians help find the small doable things that foster hope and lessen isolation and abandonment, mindful of the limits of their medical expertise. Surprisingly these modest hopes and faltering acceptances often provide a different form of strength and comfort to sustain a family.